Rate and Outcomes of Re-Admission for Rehabilitation in the Thai Red Cross Rehabilitation Center: A Retrospective Study - Konjen, Nipaporn; Krajangta, Pratana (ASEAN Journal of Rehabilitation Medicine, 2022)
Objectives: To study the rate of re-admission and functional outcomes in re-admitted patients of the Thai Red Cross Rehabilitation Center during the period 2015-2019. Study design: Retrospective study. Setting: The Thai Red Cross Rehabilitation Center, Samut Prakan Province, Thailand.. Subjects: All admitted patients who were re-admitted during the period 2015-2019. Pediatric patients and Thai Red Cross Patrons admitted primarily to provide relief of the burden on caregivers were excluded from the functional outcome analysis. Methods: Rates of re-admission were calculated from all admitted and re-admitted patients during the study period. After excluding pediatric patients and Thai Red Cross patrons, medical records of the remaining patients were extracted and their demographic characteristics, clinical data and functional outcomes from the first and the last admissions were reviewed and analyzed. Results: During the study period, 1,438 patients were admitted of whom 460 patients (32.0%) were later re-admitted. After excluding 271 patients who did not meet the study criteria, 48.2% of the remaining 189 patients had been re-admitted only once. The most common diagnosis at initial admission was stroke (48.2%). Both duration from onset to the last re-admission and diagnostic categories were significantly associated with the number of re-admissions (p < 0.001). At the last re-admission, some patients showed improvement in ambulation (29.1%), in disability level based on the modified Barthel Index (23.8%), in dynamic sitting balance (16.9%) and in static sitting balance (15.3%). Conclusion: The re-admission rate at the Thai Red Cross Rehabilitation Center during the 2015-2019 period was 32.0%. Stroke patients had the highest rate of re-admission. At the last rehabilitation re-admission, some patients had gained functional improvement and nearly 30% had improvement in ambulation.